2015
DOI: 10.1074/jbc.m114.597229
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PCSK9 Transcription by Berberine Involves Down-regulation of Hepatic HNF1α Protein Expression through the Ubiquitin-Proteasome Degradation Pathway

Abstract: Background: Berberine inhibits PCSK9 transcription via the HNF1 binding site of the PCSK9 promoter, but the underlying mechanism is unclear. Results: Berberine inhibits PCSK9 expression by inducing proteasomal degradation of hepatic HNF1␣ protein. Conclusion:The ubiquitin-proteasomal system is intrinsically connected to the PCSK9-LDLR pathway through regulation of HNF1␣ protein stability. Significance: We have uncovered a new aspect of PCSK9 regulation by ubiquitin-induced proteasomal degradation of HNF1␣.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 43 publications
(39 reference statements)
3
88
0
Order By: Relevance
“…HNF-1a was localized primarily in the nucleus, but also to a certain extent in the cytoplasm, as is consistent with the findings of Dong et al (2015). Our immunofluorescence study revealed that WT NS5A (1-126), but not NS5A V121A (1-126), was colocalized with HNF-1a in the perinuclear region (Fig.…”
supporting
confidence: 79%
“…HNF-1a was localized primarily in the nucleus, but also to a certain extent in the cytoplasm, as is consistent with the findings of Dong et al (2015). Our immunofluorescence study revealed that WT NS5A (1-126), but not NS5A V121A (1-126), was colocalized with HNF-1a in the perinuclear region (Fig.…”
supporting
confidence: 79%
“…Levels of hamster serum proprotein convertase subtilisin/ kexin type 9 (PCSK9) were measured using the Mouse PCSK9 Quantikine ELISA kit (R&D Systems) (26). Briefly, serum samples were diluted 1:10 in Calibrator diluent and allowed to bind for 2 h onto microplate wells that were precoated with the capture antibody.…”
Section: Detection Of Hamster Pcsk9 In Serummentioning
confidence: 99%
“…Thus, the interaction of two transcription factor with their binding sequence of PCSK9 promoter is reduced, and PCSK9 transcription is repressed [87] . Recently, in vivo studies using hyperlipidemic mice suggested that the serum PCSK9 concentrations decreased by 50%, that the mRNA level of PCSK9 in all liver samples decreased by 46%, and that the LDLR protein levels increased by 67% in the BBR compared with the control, whereas the mRNA levels of LDLR and other SREBP2 target genes were unchanged [86] . BBR treatment reduced HNF1α protein levels by 42% compared with control, whereas HNF1α mRNA levels were unaffected by BBR treatment.…”
Section: Berberine (Bbr)mentioning
confidence: 99%
“…These results were consistent with those obtained for a hyperlipidemic hamster. By blocking the ubiquitin proteasome system (UPS) and the autophagy-lysosomal pathway, BBR inhibited HNF1α-mediated PCSK9 transcription via UPS to decrease the hepatic HNF1α protein levels without affecting the mRNA levels [86] . Several studies have also reported that BBR has neuroprotective effects (such as suppressed neuronal apoptosis [88] and neuroinflammation [89] ) and both anti-apoptotic and antiinflammatory effects [90,91] .…”
Section: Berberine (Bbr)mentioning
confidence: 99%
See 1 more Smart Citation